THE EFFECT OF EDUCATION, DISCIPLINE, AND PERFORMANCE ON JOB SATISFACTION AT THE COMPANY - Sutarman; Ahmaddien, Iskandar; Sukmaya, Syahrul Ganda; Ida Ayu, Ma’mun Mu’min; Maharani , Kartika (International Journal of Psychosocial Rehabilitation, 2020)
Employee education, employee discipline, and employee performance have a positive and significant effect on job satisfaction, with a t.count value of 3.112 and a significant value of 0.002, and with a significance limit < 0.05, then Ho is rejected, and Ha is accepted. Work discipline has no individual relation on employee performance, with t.count of 0.864 and significant value of 0.390, and with a significance limit < 0.05, then Ho is accepted, and Ha is rejected. Job satisfaction has no particular effect on employee performance, with t.count of 0.228 and significant value of 0.820, and with a significance limit < 0.05, then Ho is accepted, and Ha is rejected. Based on the results, it is found that the adjusted R2 is 0.090, this means that 9% of dependent variables are influenced by independent variables consisting of variables of educational backgrounds, work discipline, job satisfaction. Employee education, work discipline, job satisfaction do simultaneously affect on job satisfaction at the company, which is based on the results of the regression test, it is found that the independent variables are normally distributed.